THE HISTORY OF HINDUISM AND ISLAM IN INDONESIA: A REVIEW ON WESTERN PERSPECTIVE - Rani, Mohd. Zariat Abdul (Makara Human Behavior Studies in Asia, 2010)
This article takes as its starting point the early observation that describes the vastness of the research corpus on the cultural history of Indonesia. The vastness of this corpus is, among other things, contributed to by the writings of Western scholars. Among those that are considered classics and frequently used as important references are De HindoeJavaansche Tijd by N.J. Krom (1950), Nusantara: A History of Indonesia by Bernard H.M. Vlekke (1959), and Indonesia: Trade and Society by J.C. Van Leur (1955). Initial readings find that these Western scholars’ writings often raise the question of the role and contribution of Hinduism and Islam in Indonesia. This draws attention to their views and standpoint as Westerners on the history of Indonesian culture, especially in the context of comparison between Hinduism and Islam. This article is written with the purpose of discussing the role and contribution of Islam and Hinduism in the history of Indonesia according to the perspective of three Western scholars, namely N.J. Krom, Bernard H.M. Vlekke and J.C. Van Leur in the writings mentioned above. This discussion finds that these writings studied are more inclined to acknowledge the significance of the role and contribution of Hinduism in the history of Indonesian culture, with the presence of Islam said to have not reduced the influence of Hinduism.